2012
DOI: 10.1155/2012/382603
|View full text |Cite
|
Sign up to set email alerts
|

Study on Pore Distribution and Formation Rule of Sepiolite Mineral Nanomaterials

Abstract: Theoretical research and specific surface area analysis of nitrogen adsorption indicated that a lot of structural micropores exist in sepiolite minerals fibers. However, the microporous size, existing form, and the distribution relationship between microporous structures were not proved yet. In this paper, the section TEM samples of nanofibers were prepared on the basis of the metal embedding and cutting technique, and the inner structure of sepiolite nanofibers was observed by TEM. The results showed that sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…1C) showed that the average pore diameter was around 4 nm, which was coherent with previously reported data for this type of clay. 48,49 No appreciable differences were observed in the prole of the support and the supported nickel catalysts. Regarding to the pore distribution of the Ni supported catalysts (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…1C) showed that the average pore diameter was around 4 nm, which was coherent with previously reported data for this type of clay. 48,49 No appreciable differences were observed in the prole of the support and the supported nickel catalysts. Regarding to the pore distribution of the Ni supported catalysts (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Finally, the sepiolite free Ni catalyst had a low surface area of only 7 m 2 g À1 , being this value close to that obtained by others authors in bulk Ni catalysts. 48,49 Fig . 2 shows XRD patterns of the Ni-based catalysts and their NiO precursors before and aer the reduction step.…”
Section: Resultsmentioning
confidence: 99%
“…As it is well known, if sepiolite is heat treated structural modifications due to the loss of water molecules are observed. Preisinger [72] reported that the loss of the bound H2O leads to a phase change during which the structure is folded by rotation of the phyllosilicate ribbons. These ribbons rotate around an axis through the Si-O-Si corner bonds which link the ribbons (Figure 2B).…”
Section: Characterization Resultsmentioning
confidence: 99%
“…The dimensions of the channels are ∼0.4 nm × 1.08 nm (Fig. 4b) (Helmy & de Bussetti, 2008;Suárez & Romero, 2012;Tang et al, 2012) whereas the size of the PHE molecule is 1 nm in aqueous solution (Huang et al, 1996). Thus, accommodation of the PHE molecule in the sepiolite channels might be hampered because of size.…”
Section: Main Adsorption Mechanismmentioning
confidence: 99%